EReefs modelling suggests Trichodesmium may be a major nitrogen source in the Great Barrier Reef. (31st May 2023) - Ani, Chinenye J.; Smithers, Scott G.; Lewis, Stephen; Baird, Mark; Robson, Barbara
Abstract: Trichodesmium can fix nitrogen that is later released into the water column. This process may be a major source of 'new' nitrogen in the Great Barrier Reef (GBR), but to date this contribution is poorly resolved. We have estimated the seasonal, spatial and annual contributions of Trichodesmium to the annual nitrogen budget of the GBR using the eReefs marine models. Models were run for the interval December 2010 to November 2012. During this period La Niña conditions produced record rainfalls and widespread flooding of GBR catchments. Model outputs suggest nitrogen fixation by Trichodesmium in the GBR (which covers about 348, 000 km 2 ) contributes approximately 0.5 MT/yr, exceeding the total average annual riverine nitrogen loads (0.05–0.08 MT/yr). Nitrogen fixation loads are exceeded by riverine loads only if the comparison is restricted to inshore waters and during the wet season. The river pollution is likely to have impacts in freshwater wetlands, mangroves, seagrasses and in-shore coral reefs; while Trichodesmium blooms are likely to be less intense but more widespread and affect offshore coral reefs and other oceanic ecosystems. Phosphorus and iron are suggested to be potential drivers of Trichodesmium growth and nitrogen fixation. This result is provisional but reinforces the need for more detailed assessment and reliable quantification of the annual nitrogen contribution from nitrogen fixation in the GBR and other coastal waters. Such advances will improve understandings of the role of terrestrial nitrogen loads in the GBR and of terrestrial phosphorus and iron loads which can modulate Trichodesmium abundance. These findings will help to broaden the focus of water quality management programmes and support management to improve GBR water quality. Highlights: Trichodesmium may be a major nitrogen source in the Great Barrier Reef. Nitrogen from Trichodesmium was quantified using eReefs marine models. Nitrogen fixation by Trichodesmium in the Great Barrier Reef contributes ∼ 0.5 MT/yr. Total annual fixed-nitrogen load exceeds mean riverine nitrogen inputs. Phosphorus and iron drive Trichodesmium growth and nitrogen fixation.